Agenda dynamics in Latin America: theoretical and empirical opportunities - Baumgartner,Frank R. (2020)
Abstract The Comparative Agendas Project (CAP) collects, organizes, and makes freely available millions of bits of information concerning the objects of government attention over long periods of time (often back to the Second World War) for more than 25 political systems, worldwide. As researchers affiliated with the CAP expand their projects into Latin America, they confront some challenges similar to those from other regions, and some unique to their national political systems. In this introductory essay, we explore the background of the CAP and the opportunities posed by its expansion into Latin American political systems.